Perkembangan Pasar Modal Syariah dan Pengenalan Produk Syariah di Pasar Modal - Fadillatunnisa Fadillatunnisa; Adinda Rizki Fadilah; Maryam Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This article contains the development of the Islamic capital market and the introduction of Sharia products in the capital market. The purpose of this article is to determine the development of the Islamic capital market and the introduction of Islamic products in the capital market. The Islamic capital market is a capital market whose entire mechanism of activity, especially regarding issuers, the types of securities traded and the trading mechanism, are in accordance with sharia principles. Meanwhile, what is meant by sharia securities are securities as referred to in the laws and regulations in the capital market sector whose contracts, company management and issuance methods comply with sharia principles. The data collected used in this study is secondary data. Secondary data is data taken through intermediaries or parties who have previously collected the data, in other words, researchers do not directly take their own data into the field. Secondary data is obtained from previous journal review data related to insurance, Islamic capital market development and product introduction. Sharia in the capital market. The research method used is a qualitative research method with a descriptive analysis approach. The results show that the development of the Islamic capital market has an effect on national economic growth, the importance of the role of the Islamic capital market in encouraging the rate of economic growth in Indonesia as seen from the development of the Islamic capital market will affect macroeconomic indicators such as the real exchange rate, inflation rate and growth. economy as measured by real gross domestic product. Sharia products in the capital market are sharia shares, sukuk and sharia mutual funds.